2007
DOI: 10.1080/10731190701378568
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses in Swine Resuscitated from Severe Traumatic Hemorrhagic Shock with Hemoglobin-Based Oxygen Carrier-201

Abstract: Hemoglobin-based oxygen carrier-201 transports oxygen and improves survival in swine with hemorrhagic shock, but has potential to be immune activating. Herein, we evaluated HBOC-201's immune effects in swine with more severe hemorrhagic shock due to soft tissue injury and 55% blood volume catheter withdrawal over 15 minutes followed by fluid resuscitation at 20 minutes with HBOC-201, Hextend, or no treatment (NON) before hospital arrival. Survival rates were similar with HBOC-201 and Hextend (p > 0.05), but we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…To the contrary, it may help to attenuate the existing inflammatory symptom. Similar results were also seen in a swine model of HBOC-201, which showed that HBOC-201 had no significant adverse or beneficial effects on immune function in a swine model of moderately severe HS and severe controlled HS [14][15][16]. Our in vitro results are consistent with in vivo results in that there is no inflammatory reaction caused by addition or infusion of pPolyHb.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To the contrary, it may help to attenuate the existing inflammatory symptom. Similar results were also seen in a swine model of HBOC-201, which showed that HBOC-201 had no significant adverse or beneficial effects on immune function in a swine model of moderately severe HS and severe controlled HS [14][15][16]. Our in vitro results are consistent with in vivo results in that there is no inflammatory reaction caused by addition or infusion of pPolyHb.…”
Section: Discussionsupporting
confidence: 81%
“…Ortegon et al observed that HBOC-201 had immune-activating potential, especially enhancement of neutrophilic β 2 integrin (CD11b) expression at high concentration in vitro [13]. However, in vivo in moderate and severe controlled hemorrhagic shock (HS) in swine, with the exception of mildly increased plasma levels of the anti-inflammatory Th-2 cytokine, IL-10, HBOC-201 had minimal effects on innate immune responses [14][15][16]. As well, in trauma patients human polymerized hemoglobin (Polyheme) diminished immune activation in comparison with blood transfusions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hb and mannan both functioned as the adjuvants. As an oxygen carrier, Hb was a potential immunomodulatory protein without a significant adverse immune effect, which could regulate inflammation, cytokine secretion, and activation of macrophage in the plasma. , Mannan was a ligand of TLR-4 or TLR-2 and could be recognized via mannose receptor, dectin-2, and DC-SIGN, which induce Th1-type and Th2-type immune response. Hb and mannan could play the immunomodulatory activities in a synergistic manner. Consistently, physical administration of HM with EDIII was demonstrated to increase the immunogenicity of EDIII in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Advanced Trauma Life Support, if the bleeding rate exceeds 40% of circulating blood volume (class IV), the mortality rate is more than 30% in the clinical scenario [19]. Most investigators attempt to recreate this level of shock [12,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49](table 2). …”
Section: Types Of Modelsmentioning
confidence: 99%